2010
DOI: 10.1007/s12250-010-3114-4
|View full text |Cite
|
Sign up to set email alerts
|

Reference gene selection for normalization of PCR analysis in chicken embryo fibroblast infected with H5N1 AIV

Abstract: Chicken embryo fibroblasts (CEFs) are among the most commonly used cells for the study of interactions between chicken hosts and H5N1 avian influenza virus (AIV). In this study, the expression of eleven housekeeping genes typically used for the normalization of quantitative real-time PCR (QPCR) analysis in mammals were compared in CEFs infected with H5N1 AIV to determine the most reliable reference genes in this system. CEFs cultured from 10-day-old SPF chicken embryos were infected with 100 TCID(50) of H5N1 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 28 publications
(18 reference statements)
2
35
0
2
Order By: Relevance
“…All of the investigated genes -except ALB -could be useful as ICG, because all of them had an M factor below 1.5. Similar results were obtained by Yue et al (2010), who found the M Values in the same row with no common superscript letter differ significantly (P ≤ 0.05).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…All of the investigated genes -except ALB -could be useful as ICG, because all of them had an M factor below 1.5. Similar results were obtained by Yue et al (2010), who found the M Values in the same row with no common superscript letter differ significantly (P ≤ 0.05).…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that the stability of the investigated internal control genes is dependent on species. The best result was obtained for the RPL4 gene, confirming an earlier report where the authors chose the RPL4 and YWHAZ genes as the most appropriate for normalising gene expression in embryo fibroblast cultures (Yue et al, 2010). Also, the RPS9 and RPL27 genes were used as housekeeping genes in expression analysis in pigs (Janovick-Guretzky et al, 2007;Oczkowicz et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Quantitative PCRs were performed with the CFX96 real-time system (Bio-Rad) and prepared using iQ SYBR green Supermix (Bio-Rad). Expression levels of SSRP1 (primers GGCTCACCAAGAACATGTCA and AGTCCTGAGCTGGCCTTGTA) were normalized to RPL30 (60).…”
Section: Methodsmentioning
confidence: 99%